Expression patterns of markers of inflammation, endothelial dysfunction and platelet activation in early phase of acute coronary syndrome - Tiong, Wen Ni. (Universiti Malaysia Sarawak (UNIMAS), 2012)
Inflammation, endothelial dysfunction and platelet activation play an important role in pathogenesis of vulnerable plaques of acute coronary syndrome (ACS). However little is known about the inter-relation of these in early phase of ACS. This study sought to determine a possible multimarker strategy by linking three indices to provide an early assessment of the risk of ACS. Serum protein and gene expression level of interleukin-6 (IL6;biomarker of inflammation), von willebrand Factor (VWF; biomarker of endothelial dysfunction) and soluble P-selectin (SELP; biomarker of platelet activation) were measured in 22 patients with ACS (age 55.2+10.4 years) and 28 controls with angiographically documented occlusive coronary atery disease (CAD) without previous ACS events (age 53.5+8.4 years).